Factors Associated with Poorer Post-Abortion Care Quality at Ouidah-Kpomassè-Tori Bossito District Hospital in Benin, 2022 - Mongbo Virginie; Saizonou Jacques; Fandohan Bethel; Dhezonga Chau Achille (Masters Program in Public Health, 2023)
Background: Managing abortion-related complications remains a health concern despite the insertion of postabortion care into Benin's family health service guidelines and protocols, not with standing that abortion up to 12 weeks of pregnancy has been legalized in Benin. This study aimed to investigate factors associated with poor quality of postabortion care in the Ouidah-Kpomassè-Tori-Bossito district hospital in 2022. Subjects dan Method: This was a cross-sectional, analytical study carried out from March 21 to April 8, 2022. Records of all patients admitted for abortion at Ouidah-Kpomassè-Tori-Bossito district hospital from January 1, 2021, to April 8, 2022, were reviewed, as well as the providers involved in postabortion care and administrative staff, chosen through a reasoned choice. The dependent variable was the quality of postabortion care, defined by the six components: interview, physical examination, complementary examination, diagnosis, treatment and follow-up; according to the Benin postabortion care guidelines. Independent variables were provider features, patient features, and abortion features. Information collected through literature review and questionnaire survey was analyzed using STATA 15 software. Associated factors were then identified by bivariate analysis and multiple logistic regression at 5% threshold. Results: A total of 130 records of women admitted for abortion were evaluated. The mean age was (Mean= 27.56; SD= 7.33). Postabortion care was poor in 39.23% and good in 60.77% of the patients. Factors associated with this poor quality of postabortion care were religion (p= 0.021), abortion history (p= 0.012), miscarriage history (p= 0.026) and abortion type (p= 0.007). Conclusion: Addressing these factors will help ensure a better quality of postabortion care in order to support legalized abortion and significantly reduce maternal mortality related to abortion in Benin. Keywords: postabortion care, associated factors, Benin Correspondence: Mongbo Virginie. Department of Policies and Health Systems, Regional Institute of Public Health of Ouidah, University of Abomey-Calavi, Benin. Email: vmongade@yahoo.com. Mobile: 00229 95403790.